The role of complement C1q in atrial fibrillation: a marker for disease progression and surgical outcomes - Ju, Yuefeng; Wang, MaoJing; Ji, Yang; Wang, Zhihui; Wang, Wenzhuo; Liu, Feiyue; Zhao, Qing (Frontiers in Cardiovascular Medicine, 2025)
Background and objectiveThe complement system plays a crucial role in the pathogenesis and progression of cardiovascular diseases. C1q, a key initiator of the classical pathway, is closely associated with various chronic inflammatory conditions. This observational study aims to elucidate the potential risk relationship between serum complement C1q levels and atrial fibrillation (AF).Materials and methodsThis retrospective cohort study included 812 AF patients treated at the Affiliated Hospital of Qingdao University from January 2020 to October 2022, comprising 694 patients in the paroxysmal AF group and 118 in the persistent AF group. Serum complement C1q levels were measured using an enzyme-linked immunosorbent assay (ELISA).ResultsSerum C1q levels in the AF group were significantly lower than those in the control group (P < 0.001). Logistic regression analysis indicated that reduced plasma C1q levels were independently associated with the incidence of AF (95% CI = 0.974–0.981, P = 0.001). Additionally, ROC curve analysis confirmed the close association between plasma C1q levels and AF, highlighting the predictive value of C1q for AF. Further investigation revealed that C1q serves as an independent risk factor for complex fractionated atrial electrograms (CFAE) in the superior left atrium of paroxysmal AF patients (95% CI = 0.984–0.998, P = 0.031), suggesting its potential as a clinical indicator for guiding AF surgical interventions.ConclusionSerum C1q levels are significantly reduced in patients with AF. The presence of CFAE in the superior left atrium of paroxysmal AF patients may be potentially associated with C1q levels. Low complement levels are associated with atrial fibrillation compared to individuals without AF and may represent a potential underlying cause of impaired sinus rhythm maintenance following pulmonary vein isolation. Complement C1q may play a critical role in the pathogenesis of AF.